Improving efficiency in a hybrid warehouse: a case study - Freitas, Andreia M. (2020)
Logistics has assumed a determining position in the supply chain of each organization. This paper concerns the work carried out in a bus manufacturing organization with the aim of improving efficiency in its hybrid warehouse. A hybrid warehouse could be considered as one that mixes several different activities (reception, storage area, picking, shipping, supply to production lines and production preparation tasks) and brings together many different materials or raw materials and components. This factor led to the appearance of innumerable management methods to improve employee performance. These are intended to meet the needs of their customers, from the motto "do more with less". The work developed in a hybrid warehouse allows to detect logistic complaints related to communication failures between employees, the reduced efficiency in the activities like the check of raw materials or components and respective picking, the lack of space for their reception and storage, and the non-compliance of the FIFO stock management system. It is imperative that organizations can redefine internal spaces and flows, generating a more efficient and intuitive work and admit an opportunity for improvements in terms of space and content management, and hence, cost savings for an organization. The combination of Lean tools was implemented, and the results have been checked, showing a significant impact in the hybrid warehouse, with annual gains through the optimization of several activities: employee turnover (decrease by 50%), check and picking times (decrease about 75 minutes/picking) and better working conditions for employees.